The Role of the TGF-β Superfamily in Myocardial Infarction - Hanna, Anis; Frangogiannis, Nikolaos G. (Frontiers in Cardiovascular Medicine, 2019)
The members of the transforming growth factor-beta (TGF-beta) superfamily are essential regulators of cell differentiation, phenotype and function, and have been implicated in the pathogenesis of many diseases. Myocardial infarction is associated with induction of several members of the superfamily, including TGF-beta1, TGF-beta2, TGF-beta3, bone morphogenetic protein (BMP)-2, BMP-4, BMP-10, growth differentiation factor (GDF)-8, GDF-11 and activin A. This manuscript reviews our current knowledge on the patterns and mechanisms of regulation and activation of TGF-beta superfamily members in the infarcted heart, and discusses their cellular actions and downstream signaling mechanisms. In the infarcted heart, TGF-beta isoforms modulate cardiomyocyte survival and hypertrophic responses, critically regulate immune cell function, activate fibroblasts, and stimulate a matrix-preserving program. BMP subfamily members have been suggested to exert both pro- and anti-inflammatory actions and may regulate fibrosis. Members of the GDF subfamily may also modulate survival and hypertrophy of cardiomyocytes and regulate inflammation. Important actions of TGF-beta superfamily members may be mediated through activation of Smad-dependent or non-Smad pathways. The critical role of TGF-beta signaling cascades in cardiac repair, remodeling, fibrosis and regeneration may suggest attractive therapeutic targets for myocardial infarction patients. However, the pleiotropic, cell-specific and context-dependent actions of TGF-beta superfamily members pose major challenges in therapeutic translation.